Communication Identity of Maize Farmers in the Digital Immigrant Group in Accepting Innovation through the Utilization of Digital Petani Apps - Anisa Rahmi Lutfial Umi; Ratih Hasanah Sudrajat (Riviera Publishing, 2024)
The development of digital technology has brought significant changes in the agricultural sector, including through the peTani Apps digital application that is expected to help farmers. However, adopting this technology is not always easy, especially for farmers in the digital immigrant group. This study aims to identify and examine the process of forming a communication identity of corn farmers in the digital immigrant group who accept innovations through digital peTani Apps. The research method used is descriptive qualitative with a case study approach processed and analyzed using NVivo. The research applied Michael Hecht's Communication Theory of Identity (CTI) in farmers' interaction with new technology. The results showed that farmers' communication identity levels, including personal identity, enactment identity, relational identity, and communal identity, play a significant role in technology adoption. Personal identity resulted in the finding that many farmers felt insecure and inexperienced in using advanced technology, which led to discomfort in using the application. Enactment identity shows that peTani Apps' digital technology innovation has not become part of farmers' daily routine due to difficulties in navigation and understanding functions. Relational identity reveals that community support and social relationships are crucial in adoption. Communal identity reflects resistance to change in communities with strong traditional norms. Overall, the app has not been widely adopted by digital immigrant groups. Social, cultural, and economic factors influence the adoption rate of these technologies, so more targeted strategies and greater support are needed to encourage equitable adoption among farmers.